Gender justice, development, and rights - Molyneux, Maxine; Razavi, Shahra (Oxford studies in democratization., 2002)
This text examines contemporary issues such as neoliberal policies, democracy and multiculturalism, analyzing them from a gender perspective. It examines how liberal rights and ideas of democracy and justice have been absorbed into the political agendas of women's movements.